Feasibility of laparoscopic surgery for complex Crohn's disease of the small intestine. Issue 4 (27th April 2016) - Manabe, Tatsuya; Ueki, Takashi; Nagayoshi, Kinuko; Moriyama, Taiki; Yanai, Kosuke; Nagai, Shuntaro; Esaki, Motohiro; Nakamura, Kazuhiko; Nakamura, Masafumi
Abstract: Background: The laparoscopic approach for complex Crohn's disease (CD), which involves abscess formation, fistula formation, and recurrent CD, is controversial. The aim of this study was to investigate the feasibility and safety of the laparoscopic approach for complex CD. Methods: Fifty‐six patients who had undergone surgery for CD of the small bowel from January 2007 to August 2014 were divided into two groups: the laparoscopic approach for complex CD group (LC group, n  = 31) and the laparoscopic approach for simple CD group (LS group, n  = 25). The preoperative data and surgical outcomes of the LC group were compared with those of the LS groups. Results: There were no significant differences in preoperative data and operating time between the two groups. Blood loss was not significantly different between the LC and LS groups. The incision length was longer in the LC group than the LS group ( P  = 0.004). The incidence of severe postoperative complications in the LC group was higher than in the LS group ( P  = 0.026). The length of postoperative stay was similar in the LC and LS groups. Conclusions: The laparoscopic approach for complex CD is feasible and provides good cosmesis that is comparable to that offered by simple CD.